Development of a single-stranded DNA-binding protein fluorescent fusion toolbox. Issue 11 (6th May 2020) - Dubiel, Katarzyna; Henry, Camille; Spenkelink, Lisanne M; Kozlov, Alexander G; Wood, Elizabeth A; Jergic, Slobodan; Dixon, Nicholas E; van Oijen, Antoine M; Cox, Michael M; Lohman, Timothy M; Sandler, Steven J; Keck, James L
Abstract: Bacterial single-stranded DNA-binding proteins (SSBs) bind single-stranded DNA and help to recruit heterologous proteins to their sites of action. SSBs perform these essential functions through a modular structural architecture: the N-terminal domain comprises a DNA binding/tetramerization element whereas the C-terminus forms an intrinsically disordered linker (IDL) capped by a protein-interacting SSB-Ct motif. Here we examine the activities of SSB-IDL fusion proteins in which fluorescent domains are inserted within the IDL of Escherichia coli SSB. The SSB-IDL fusions maintain DNA and protein binding activities in vitro, although cooperative DNA binding is impaired. In contrast, an SSB variant with a fluorescent protein attached directly to the C-terminus that is similar to fusions used in previous studies displayed dysfunctional protein interaction activity. The SSB-IDL fusions are readily visualized in single-molecule DNA replication reactions. Escherichia coli strains in which wildtype SSB is replaced by SSB-IDL fusions are viable and display normal growth rates and fitness. The SSB-IDL fusions form detectible SSB foci in cells with frequencies mirroring previously examined fluorescent DNA replication fusion proteins. Cells expressing SSB-IDL fusions are sensitized to some DNA damaging agents. The results highlight the utility of SSB-IDL fusions for biochemical and cellular studies of genome maintenance reactions.